An undiagnosed case of placenta increta: a nightmare for obstetricians - Marla, Shreesha; Ganiga, Pradeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Placenta increta, one type of morbidly adherent placenta, is characterized by entire or partial absence of the decidua basalis, and by the incomplete development of the fibrinoid or Nitabuch’s layer and villi actually invading the myometrium. The major clinical problem in placenta accreta spectrum disorder is failure of placenta to separate normally from the myometrium after fetal delivery. It is associated with high morbidity and sometimes with a lethal outcome, mainly as a result of severe bleeding, uterine rupture and infections. 33-year-old Mrs. X primigravida at 38 weeks 5 days admitted in our hospital for elective LSCS with the indication of hysteroscopy and laproscopic ACUM (accessory and cavitated uterine mass) excision in the past. Adherent placenta diagnosis was done on table, senior anesthetic team was called and decision was taken to remove the placenta manually with adequate resuscitative measures i/v/o torrential bleeding. Defect of 4×6 cm on the anterolateral part of the upper uterine segment (previous ACUM excision site). Decision was done to go ahead with vigilant watch, keeping ready for systematic devascularization of the uterus followed by caesarean hysterectomy in case torrential bleeding continues. With a multidisciplinary approach, Patient was serially monitored with USG, beta hCG levels, attempting to preserve uterus in this case. This was a very rare case of asymptomatic placenta previa with placenta increta in a post ACUM scarred uterus and it was successfully managed by sequential monitoring with backed up uterine embolization team if secondary PPH occurs.